The experience of interacting: Learning communication for deaf students - Rengganis, Linangkung Diah Ayu; Suryana, Asep; Wahyudin, Uud; Yati, Sri Eka; Santoso, Budi (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
In the school environment in addition to studying teaching materials, deaf students also explore a variety of vocabulary. Teachers have a more role, in addition to helping students' understanding of communication teaching materials, it is also needed as a means of enriching vocabulary, including honing students in understanding oral communication, namely reading lip movements. The hope is that when deaf people can understand vocabulary and sign language, communication with sign language becomes equivalent to vocal communication in general which can make them confident in communicating with anyone. During the process, everything cannot be separated from the teacher's intervention in educating, exposing the material, and honing the potential of his students. Based on this phenomenon, researchers will examine the meaning of learning communication in teachers towards deaf people as research objects. This study aimed to determine the learning communication experience of deaf students at SLBN Cicendo, Bandung. It uses Symbolic Interaction Theory developed by George Herbert Mead as a guide. The approach used in this study is qualitative with a phenomenology method. The data in this study were obtained through observation, in-depth interviews, and a literature study. The results of this study indicate that learning communication in deaf students begins with the things closest to the children. These things can be experiences or what the child is thinking. The teacher as a teacher will lead the opinion on the material to be taught at that time. Then the teaching given is also adjusted to the abilities possessed by each child. The conclusion of this research is the provision of teaching materials to deaf students guided by individual learning. How to find out the best learning techniques for deaf students are obtained through the experience of interacting between classroom teachers and students.